Insights into chitosan antibioﬁlm activity against methicillin-resistant Staphylococcus aureus - Costa, E. M. (2017)
Aims: Chitosan is a natural compound that has been validated as a viable antimicrobial agent against Staphylococcus aureus. With this work we sought to evaluate the planktonic and sessile sensitivity of methicillin-resistant S. aureus to chitosan's activity and evaluate if methicillin-resistant S. aureus (MRSA) would be more or less sensitive to chitosan's activity than methicillin-sensitive S. aureus (MSSA). Methods and Results: A group comprised of reference strains and clinical multiresistant isolates of MSSA and MRSA were used. Methicilin resistance effect upon chitosan activity was assessed in planktonic setting and in different phases of sessile colonization, namely adhesion, biofilm formation and mature biofilm through biomass and metabolism inhibition. The results obtained showed that S. aureus methicillin resistance mechanism did not impair chitosan's activity as the highest bacterial susceptibility was registered for MRSA. Chitosan was highly effective in inhibiting MSSA and MRSA strains in both planktonic and sessile settings with biofilm inhibition percentages reaching as high as 90% for MRSA. Conclusions: Staphylococcus aureus methicillin resistance did not impair chitosan's antimicrobial and antibiofilm activities and MRSA and MSSA were inhibited both in planktonic and sessile settings at low concentrations with great efficacy. Significance and Impact of the Study: Considering the obtained results chitosan shows potential as an alternative for the control of biofilm-related recalcitrant MRSA infections.